Lean Supply Chain: Take an Opportunity to do More with Less - Cvetić, Biljana (Array, 2021)
The purpose of this paper is to demonstrate that the application of lean approach in supply chain can act and influence the improvement of performances of the overall supply chain, as well as of all its participants. Some of the benefits which can be achieved by applying lean tools, methods and techniques, with minimal required investment, in supply chain are: reduced wastes, reduced costs, improved quality, faster delivery, and consequently increased supply chain profitability. In this paper, the comparison of traditional and lean supply chain is done according to different derived characteristics. The identification of comparative characteristics is done by desk research in combination with conversational research. The paper can serve as a basis for transforming existing supply chain into a lean supply chain.